IMPROVING SPEAKING ACHIEVEMENT OF THE ELEVENTH GRADE STUDENTS OF SMA METHODIST 2 PALEMBANG BY USING EDMODO - Claudia Yunierta Tambunan; Ida Rosmalina; Erlina Erlina (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2017)
Abstract: The objective of this study was to find out whether or not there was any significant differencein English speaking performance of the 11th grade students of SMA Methodist 2 Palembang after being taught using Edmodo. The sample of this study was 26 eleventh grade students of SMA Methodist 2 Palembang which were taken by using convenience sampling method from the total of 136 students. This study used within- group experimental design that is one group pretest-posttest design. Two raters did the scoring for the students’ pre-test and post-test based on the rubric provided by the researcher. To collect the data, the students were given a pretest and a posttest. The  data were analyzed by using paired sample t test. The result showed: (1) there was a significant improvement in students’ speaking skill after they were taught by using Edmodo (mean diff=7.23; p-value=.000). The mean score of each aspect of speaking skill in the posttest was higher than in the pretest and p-value were <0.05, and (2) the majority of the students agreed that Edmodo was effective to use. In conclusion, Edmodo can be used to improve student’s speaking skill Key words: speaking Achievement, Edmodo, eleventh graders